Sosilaisasi Penggunaan Website Desa Bandar Pasir Mandoge Sebagai Sistem Administrasi dan Media Promosi Desa: Pengabdian - Bambang Irwansyah; Daniswara; Reza Fahlevi; Eldo Yusri; Imam Arifin; Septi Nur Selase; Fajar Hardiansyah; M. Fikri Gunawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Bandar Pasir Mandoge Village is a village within the administrative area of Bandar Pasir Mandoge District, Asahan Regency. Bandar Pasir Mandoge Village does not have a website-based administration system. Due to this problem, the village government is hampered and less than optimal in running village administration. The purpose of this community service activity is to increase the understanding of village officials and the community of Bandar Pasir Mandoge Village regarding the function and benefits of the village website as a modern administrative tool as well as a medium for promoting village potential. Through this activity, village officials are expected to be able to master the technical skills in managing and updating website content independently so that the information presented is always up-to-date and relevant. Administrative data will then be adjusted to the needs of the village. The results of the socialization of the village website with the link bandarpasirmandoge.com which was held on August 13, 2025 at the Bandar Pasir Mandoge Village Hall went smoothly and received a positive response from all participants. This activity was attended by village officials, community leaders, representatives of community organizations.